Change of Variable-Foreperiod Effects within an Experiment: A Bayesian Modeling Approach. Issue 1 (13th July 2022) - Han, Tianfang; Proctor, Robert W.
The framework of binding and retrieval in action control (BRAC) by Frings et al. (2020 ) proposed that repetition of any element in the previous trial triggers the retrieval of other elements in the same event file. Consistent with this framework, Los et al. (2014 ) argued that the temporal relation between the warning signal and the target stimulus on a trial is stored in a distinct memory trace (or, event file). Retrieval of the preceding memory trace, which is triggered by perceiving the same warning signal, leads to sequential foreperiod (SFP) effect. We modeled the data from four experiments using a Bayesian method to investigate whether the SFP effect changes over time. Results of Experiments 1, 3 and 4 support the multiple trace theory of preparation, which predicts an asymmetric sequential foreperiod effect, whereas those of Experiment 2 (extremely short foreperiods) support the repetition priming account by Capizzi et al. (2015 ). Moreover, the significance of the parameters showed that the asymmetry in Experiments 1 and 3 (non-aging distribution) developed gradually, whereas in Experiment 4 (uniform distribution), this asymmetry was significant from the beginning and did not change over time. Implications of these findings for temporal preparation models and BRAC framework were discussed.